Analisis Kerusakan Tanaman Kelapa dan Musuh alami Hama Segestes decoratus (Orthoptera: Tettigoniidae) di Indonesia [Analysis of coconut palm damage and natural enemies of the Segestes decoratus pest (Orthoptera: Tettigoniidae) in Indonesia] - Meldy L.A. Hosang; Jelfina C Alouw; Welmenci J Sambiran (Buletin Palma, 2020)
Segestes docoratus (Orthoptera: Tettigoniidae) is one of the pests that can damage coconut leaves and cause very heavy damage in the area of distribution, especially in abandoned fields in certain islands. In Indonesia, S. docoratus pest only found in the Morotai Islands, Morotai Island Regency, North Maluku Province. Detailed information on damage, the population of the pest and its natural enemies, as well as distribution are still limited. This research aims to study the damage of coconut trees, pest populations and the potential of natural enemies that can suppress pests development in the field. The study was conducted on farmers land in Darame Village, Pilowo, South Morotai District, Yao Village, Bido Village North Morotai District, Waringin Village (Small Loleba Island and Big Loleba Island), Posi Posi Rao Village (Rao Island), South West Morotai District, Regency Morotai Island, North Maluku. At each location was selected 10 trees sample, and then young frond, mature frond and old frond were taken. Plant damage, coconut production, pest and natural enemies population were observed from each sample. The results showed that the S. decoratus pest damages coconut leaves but does not damage female flowers or young fruits. These pest attacks are generally categorized as light and moderate, but in certain locations in the North Morotai District and the Village of Posi Posi Rao (Rao Island), South West Morotai District, there are plants with a heavy attack level. Nearly all locations visited had S. decoratus pest attacks, except on the islands of Small Loleba and Big Loleba. Based on the assessment of the damage to leaflets from each frond, the percentage of leaf damage is higher in older leaves than mature leaves and lowest in young leaves. The average damage to old leaves is 26.57% - 48.65%, mature leaves 10.15% - 36.97% and young leaves 8.69% - 14.88%. The nymph of S. decoratus preferred young leaves as its food compared to mature and old leaves. This was indicated by the highest nymph population on young leaves and the lowest on old leaves. On the other hand, the higher adult population was found on the old fronds than the mature fronds and lowest on young fronds. This preference might be due to different nutritional components needs between nymph and adult stages, and different nutrient profiles of coconut leaflet between young and old fronds, or the mandible strength. Mandible of the imago is typically more robust than that of the nymphs. Hence, S. decoratus nymphs preferred the soft young leaves, while imagos prefer old leaves. The Stichoterma dallatorreanum parasitoid was not found in the nymphs and adults of S. decoratus collected, but it was found in other Tettigoniidae which are not coconut pests. Other natural enemies found were a spider predator, Oecophylla smaragdina, black ants, predator birds, and entomopathogenic fungi.ABSTRAKSegestes decoratus (Orthoptera: Tettigoniidae) merupakan salah satu hama yang merusak daun kelapa dan dapat menyebabkan kerusakan yang sangat berat di daerah penyebarannya terutama pada kebun yang tidak terpelihara pada pulau-pulau tertentu. Di Indonesia, hama S. decoratus hanya ditemukan di Kepulauan Morotai, Kabupaten Pulau Morotai, Provinsi Maluku Utara. Informasi kerusakan, populasi hama dan musuh alaminya serta distribusi masih terbatas. Penelitian ini bertujuan untuk mempelajari kerusakan tanaman kelapa, populasi hama dan potensi musuh alami yang dapat menekan perkembangan hama di lapangan. Penelitian dilaksanakan pada lahan petani Kecamatan Morotai Selatan, Kecamatan Morotai Utara,  Kecamatan Morotai Selatan Barat, Kabupaten Pulau  Morotai, Maluku Utara. Pada setiap lokasi dipilih 10 pohon contoh kemudian diambil daun muda, daun tengah dan daun tua. Dari setiap tanaman contoh diamati kerusakan tanaman, populasi hama, musuh alami dan produksi tanaman kelapa. Hasil penelitian menunjukkan bahwa hama S. decoratus merusak daun kelapa tetapi tidak merusak bunga betina atau buah muda. Serangan hama ini pada umumnya dikategorikan pada  serangan ringan dan sedang, tetapi pada lokasi tertentu di Kecamatan Morotai Utara dan di Desa Posi Posi Rao (Pulau Rao), Kecamatan Morotai Selatan Barat, terdapat tanaman dengan tingkat serangan berat. Hampir semua lokasi yang dikunjungi sudah terdapat serangan hama S. decoratus, kecuali di Pulau Loleba Kecil dan Loleba Besar. Berdasarkan penilaian kerusakan anak daun dari setiap pelepah, ternyata persentase kerusakan daun lebih tinggi pada daun tua dibandingkan dengan daun tengah dan terendah pada daun muda. Rata-rata kerusakan pada daun tua 26,57 – 48,65%, daun tengah 10,15 – 36,97% dan daun muda 8,69 – 14,88%. Nimfa S. decoratus lebih memilih daun muda sebagai makanannya dibandingkan dengan tengah dan daun tua, hal ini ditunjukkan oleh populasi nimfa tertinggi pada daun mudadan terendah pada daun tua, sebaliknya populasi imago lebih banyak pada pelepah daun tua dibandingkan dengan daun tengah dan terendah pada daun muda. Preferensi ini kemungkinan disebabkan karena kebutuhan nutrisi yang berbeda antara nimfa dan imago dan perbedaan profile nutrisi dari pinak daun pada pelepah daun yang muda dan tua, sertamandibel nimfa masih lunak sehingga memilih daun yang masih muda sedangkan mandibel imago lebih kuat. Dari nimfa dan imago S. decoratus yang dikoleksi, tidak ditemukan parasitoid Stichoterma dallatorreanum tetapi ditemukan pada Tettigoniidae lain yang bukan hama kelapa. Ditemukan  predator laba-laba, Oecophylla smaragdina,  semut hitam, burung predator dan cendawan entomopatogen.